Politics and public enterprises the case of PERNAS in Malaysia - Gale, Bruce (1979)
The political role of public enterprises in Southeast Asia is often overlooked. The case of PERNAS, a Malaysian public enterprise committed not only to the implementation of general policies designed to develop the Malaysian economy, but also to encouraging participation of the indigenous Malays (Bumiputras) in the nation's commerce and industry, illustrates the interplay of economic and social as well as political factors in the domestic and foreign matters. For instance, its political masters used the Corporation not only to implement controversial economic policies, but also to further entrench themselves within the hierarchy of the dominant party in the National Front coalition. Meanwhile, foreign governments, as illustrated by the Corporation's involvement in the China trade and the Haw Par deal, reacted in ways which supported the contention that "in many Third World countries, public enterprises are not and cannot be the apolitical servants of their political masters."
Keywords: Government business enterprises -- Malaysia; Public administration -- Economic aspects; Public administration -- Malaysia